Stone tools from the fallow ground of Na Rojah near Mirna in Lower Carniola - Jamnik, Pavel (Arheološki vestnik, 2000)
The article discusses a find of stone tools from the fallow ground of Na Rojah near Mirna. From a total of 1370 collected flint fragments, 152 examples of lithic industries were chosen, 23 of them typologically determinable tools. At the same site, 35 fragments of pottery were also found, which need not be directly related to the stone artifacts. The cultural classification suddenly is no longer certain.